STUDI OBSERVATIF TERHADAP RAGAM HAMBATAN PADA WAWANCARA REFERENSI SECARA TATAP MUKA DAN VIRTUAL - RattahpinnusaH Handisa, Rattah H Handisa (LIBRIA, 2018)
Interviewing patrons is very challenging in a reference service. Not only internal factors may influence the interview, but also external factors may obstruct the reference interview. The purpose of this research is to identify challenges of reference interview and to evaluate the findings, such as: interviewing process, searching strategy, legal issues and effectivity of face to face reference interview and virtual reference interview. This research involved three participants who act as an observer, a face to face interviewee and a virtual interviewee. The data on the face to face interview were collected by using open questions in the questionnaire. Meanwhile, the data on the virtual interview were collected by using Goggle Hangsout. The assessment criteria for librarian include the behavioural performance, the implementation reference service and the provision service and privacy. Findings showed that the observer found several challenges in face to face and virtual interview. The challenges on both face to face interview and virtual interview were identified as following lists: over use open question lead to the lack clarity of interviewee’s respond in reference interview, the result of the librarian’s performance showed that the librarian did not follow the guidelines section 3.1.8 in the face to face interview because the librarian tended to over use open question without clarification. Furthermore, the librarian failed to manage time in the virtual interview due to technical problem. The librarian took time more than twenty minutes conduct the virtual interview